The Ideological Roots of Populist Radical-Right Climate Scepticism: A Qualitative Data Analysis of the Case Vlaams Belang - Praet, Jasper (Politics of the Low Countries, 2025)
The study of populist radical-right parties has boomed in recent years. Analyses of the discourse of these parties have gone beyond the focus of immigration policies and have turned to their climate communication. Previous research identified populism and the radical-right host ideology as key ideological drivers of their climate scepticism. This study questions which of these ideological features are dominant in the climate discourse of the Belgian populist radical-right party Vlaams Belang. A qualitative data analysis shows that their ideology is most aptly described as conservative and authoritarian. Populism is not salient, in contrast to what previous research has found for other populist radical-right parties. The presence of nationalism is confirmed, but nativism is irrelevant. The results indicate that Vlaams Belang adapts and transplants its core ideology to its climate discourse, but we cannot take the prevalence of populism or nativism in their climate discourse for granted.